Reforming Indonesia's Approach to Transfer of Sentenced Persons: A Maqāṣid al-Sharīʿa Framework and a Comparative Analysis of ASEAN and European Models - Sriwidodo, Joko; Saputra, Rahmat; Widodo, Akmal Alfarisi (Invest Journal of Sharia & Economic Law, 2025)
This study examines the legal and humanitarian challenges faced by Indonesian migrant workers imprisoned abroad and the urgency of establishing a clear legal mechanism for the transfer of sentenced persons (ToSP) between Indonesia and other countries.  ​Recent cases from Myanmar, Malaysia, and Saudi Arabia reveal persistent gaps in Indonesia's legal framework, leaving migrant workers vulnerable to unjust criminalization, disproportionate punishment, and prolonged detention without a predictable pathway for repatriation. The study finds that Indonesia's current approach relies heavily on ad hoc diplomatic negotiations rather than enforceable legal procedures, contravening the rehabilitative and humane treatment principles enshrined in international conventions, such as UNCAC Article 45 and UNTOC Article 17. Comparative analysis further reveals the absence of an ASEAN-wide prisoner transfer mechanism, unlike the comprehensive European Convention on the Transfer of Sentenced Persons. To address these deficiencies, this study proposes a two-pronged reform agenda: enacting a dedicated Indonesian National Law on ToSP and advocating an ASEAN Protocol on Prisoner Transfer. Crucially, the study reinterprets the issue through the lens of maqāṣid al-sharīʿa, positioning the protection of migrant workers' lives (ḥifẓ al-nafs), family well-being (ḥifẓ al-nasl), and economic welfare (ḥifẓ al-māl) as ethical imperatives that transcend the procedural limits of positive law. This maqāṣid-based framework transformed the ToSP regime from diplomatic discretion to a legally mandated restorative justice mechanism. The study concludes that aligning Indonesia's domestic legislation, bilateral agreements, and ASEAN advocacy with maqāṣid principles would establish a more humane, rehabilitative, and socially responsive transnational criminal justice system for migrant workers.